The Effect of Multi-Scale Faults and Fractures on Oil Enrichment and Production in Tight Sandstone Reservoirs: A Case Study in the Southwestern Ordos Basin, China - Zeng, Lianbo; Lyu, Wenya; Zhang, Yunzhao; Liu, Guoping; Dong, Shaoqun (Frontiers in Earth Science, 2021)
The Chang 8 Member of the Upper Triassic Yanchang Formation in the southwestern Ordos Basin is a typical tight sandstone reservoir. Multi-scale faults and fractures are widely developed in these reservoirs. In this study, three-dimensional seismic data, outcrops, cores, imaging logs, and thin sections are used to classify faults and fractures at multiple scales. Combined with the oil production data, the influence of multi-scale faults and fractures on the oil enrichment and production was analyzed. The results show multi-scale faults and fractures can be divided into six levels: type-I faults, type-II faults, large-scale fractures, mesoscale fractures, small-scale fractures, and micro-scale fractures. As the scale decreases, the number of fractures increases in a power function. Type-I faults cut the caprocks and are not conducive to the preservation of oil. Type-II faults connect the source rocks and reservoirs and are migration channels of the oil source. Large-scale fractures cut the mudstone interlayer and are the seepage channel inside the reservoir. Mesoscale fractures are controlled by thick interlayers, and small-scale fractures are restricted by thin interlayers or layer interfaces. These fractures are the main seepage channels and effective storage spaces. Micro-scale fractures serve as important storage spaces for these reservoirs. The development example proves that type-I faults contribute the most to the fluid flow, while the oil production of wells drilled into type-II faults is higher. The oil production changes with the development degree of fractures in different scales, strikes, and positions of faults. Meso- and small-scale fractures are the key to influencing the early single-well production, and micro-scale fractures are conducive to the stable production of single wells. Consequently, multi-scale faults and fractures have significantly different effects on the oil enrichment and production of tight sandstone reservoirs, and the research results can refer to the exploration and development of these reservoirs.